Support Your Recovery Needs (SYRN) - a systemic approach to improve sport performance - Adamczyk Jakub Grzegorz (Sciendo, 2023)
Study aim: The aim of this study was to present the Support Your Recovery Needs (SYRN) recovery system based on scientifically confirmed methods, addressing the needs of athletes based on their subjective feelings of fatigue after training or competition.